International Innovation and Labor Management: Insights into Sales Productivity at EPSON Perú - Cruz Padilla, Jorge Martín; Calderón Saldaña, Jully Pahola; Alzamora De Los Godos, Luis; Valladolid Marcos, Fiorella Sthefany; Pineda Medina, Javier Alejandro; De La Rosa Condormango, Rossina Dany; Barrios Cabello, Lucimar Josefina (LACCEI, 2025)
This interpretative research explores the relationship between labor competency management and sales productivity within the framework of international innovation and entrepreneurship. A longitudinal, analytical study was conducted at EPSON Perú, a transnational technology company, using a validated questionnaire administered to 120 sales promoters between 2020 and 2021. While no statistically significant association was found between productivity and core competency strategies—such as the Delta model, integrated customer solutions, or benefit-based competency frameworks—the analysis revealed meaningful patterns in subdimensions like comparative competency profiling and optimal information use. These insights suggest that, in international innovation-driven environments, productivity may depend more on adaptive and contextual management practices than on standardized competency models. The findings highlight the complexity of workforce productivity and underscore the need for dynamic and innovation-oriented human capital strategies in competitive global markets.